Does children’s communal self-perception mediate the relationship between their gender and their communal career aspirations? ... - Kvalø, Marie; Thorsteinsen, Kjærsti; Olsen, Marte; Martiny, Sarah E. (OSF Registries, 2020)
The study is a follow-up study from a study conducted in kindergartens in Tromsø in 2018 (Olsson, Martiny & Steffens, 2020). The sample consisted of 159 participants (84 boys, 75 girls) between 4 and 6 years of age (M = 5.50, SD = 4.45). The study aimed to investigate the effect of gender stereotypes and communal self-perceptions (the behaviors one identifies with, e.g. comforting, helping) on kindergarten children’s career aspirations. The authors found that descriptive gender stereotypes tended to increase girl’s aspirations towards communal occupations, but not for boys. The authors also used a mediation model with gender as the predictor, communal aspirations as the outcome and communal self-perceptions as the mediator. This study found that gender predicted communal self-perceptions, and communal self-perceptions predicted career aspirations, but gender did not independently predict career aspirations. The authors also found that girls in general have more communal self-perceptions. This means that ...